Causes and Impacts of Foreign Labour Migration on Household Economy (Journal of Population and Development, 2021)
This paper based on impact of foreign labour migration on household economy of Gauradaha municipality, ward no. 4 Jhapa district. The aims of this paper are to identify the causes and impacts of labor emigration in the place of their origin. It is a cross sectional and descriptive study with primary source of data. Study selected 132 household and 145 numbers of form fill up within one month and have used purposive sampling method (non-probability sampling). At last, SPSS (Statistical Package for the Social Sciences) program is used to compute the data. Frequency distribution, and cross table analysis are the main output of the analysis. The analysis has been done on the basis of data generated from the interview, the study has revealed unemployment, Poverty, lacks of opportunity in the home country is the reasons and obligations of labour migration. Gulf countries followed by East/South-East Asian countries have been the major destination of migrant workers. Due to the lack of higher education and proper training, they face problem in languages, skilled and are compelled to work as unskilled manual workers. Therefore, they have been working abroad in lower wage and salary due to the lesser skills. Bank and Hundi/IME are the major sources to transfer the remittances to their households. To buy essential goods and maintain the house expenses have been the first priorities of using the remittances. Besides, they have invested on education of their children and constructing houses.